2019
DOI: 10.7554/elife.40712
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and topological reorganizations in mitochondrial architecture interplay during Bax-mediated steps of apoptosis

Abstract: During apoptosis, Bcl-2 proteins such as Bax and Bak mediate the release of pro-apoptotic proteins from the mitochondria by clustering on the outer mitochondrial membrane and thereby permeabilizing it. However, it remains unclear how outer membrane openings form. Here, we combined different correlative microscopy and electron cryo-tomography approaches to visualize the effects of Bax activity on mitochondria in human cells. Our data show that Bax clusters localize near outer membrane ruptures of highly variabl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(57 citation statements)
references
References 77 publications
1
48
0
Order By: Relevance
“…Furthermore, compared with healthy mitochondria, the matrix of apoptotic mitochondria is more dilute 106 . Potentially, the extra pressure associated with the increased volume of a more dilute matrix may be an important driver of both macropore expansion and inner mitochondrial membrane extrusion and subsequent rupture.…”
Section: [H2] Mechanisms and Consequences Of Momp-driven Inflammatorymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, compared with healthy mitochondria, the matrix of apoptotic mitochondria is more dilute 106 . Potentially, the extra pressure associated with the increased volume of a more dilute matrix may be an important driver of both macropore expansion and inner mitochondrial membrane extrusion and subsequent rupture.…”
Section: [H2] Mechanisms and Consequences Of Momp-driven Inflammatorymentioning
confidence: 99%
“…This was unexpected because cGAS and STING reside outside the mitochondria, whereas mtDNA localises to the mitochondrial matrix and the inner mitochondrial membrane was thought to remain intact during apoptosis. Various studies employing different imaging approaches in murine embryonic fibroblasts as well as various cancer cell lines have addressed how mtDNA could be exposed to cGAS-STING [104][105][106] . Super-resolution imaging of cells undergoing mitochondrial apoptosis demonstrated that MOMP induction is followed, over time, by the formation of expanding pores on the mitochondrial outer membrane.…”
Section: [H2] Mechanisms and Consequences Of Momp-driven Inflammatorymentioning
confidence: 99%
“…In the case of programmed cell death, the activation of the Bax/Bak pathway may induce permeabilization of the outer mitochondrial membrane with the formation of pores that, under prolonged stress, become deeper until reaching the inner mitochondrial membrane. Via these structures, mtDNA nucleoids (i.e., mtDNA complexed with the mitochondrial transcription factor A) can be displaced into the cytosol [37,38,65]. Altered mitochondrial dynamics have also been associated with mtDNA-driven inflammation [34][35][36]39,40].…”
Section: Failing Mitochondrial Quality Control and Mtdna Releasementioning
confidence: 99%
“…Despite a growing number of successfully reported in-cell cryo-ET studies 4,9,[15][16][17][18] , controlled on-grid positioning of adherent mammalian cells has remained largely unaddressed. Currently, optimization of grids for cellular cryo-ET is primarily carried out by adjusting the concentration of the cell suspension during seeding.…”
mentioning
confidence: 99%